Expected render performance assessment based on impact resistance in situ determination - Inês Flores-Colen (2009)
External renders must fulfil certain functions to ensure a good in-service performance of façades such as: waterproofing and protection of the walls, finishing of the surfaces, durability in face of the external degradation agents, and adequacy to use. Defective surface resistance of the renders (significant deteriorationunder impact and friction actions inherent to the normal use of the building) accelerates the degradation process, leading to a significant loss of physical and aesthetical performance. Based on laboratory experimental testing and on-site investigation, with various types of renders and using the Martinet-Baronnie device, the parameters of surface resistance are discussed, in terms of resistance to the impact of hard objects (with and without cutting edges). The results allowed criteria to be proposed for the in situ assessment of external renders in buildings with brick masonry walls (characterization of predicted surface impact resistance in-service conditions).